Uncertainty as an epistemic and pedagogical value of educational and formative ecosystems in the pedagogical anthropology of E. Morin: Field experience and a new paradigm in education - Vincenzo Salerno; Leonardo Rigoni (Pensa MultiMedia, 2022)
E. Morin has been declaring for a long time that radical changes in pedagogical paradigm and educational actions are needed, especially due to the pandemic crisis, which has led to a rediscovery of uncertainty in our life. For this reason, it is necessary to start reflecting on this experience as an educational category, both at an epistemological and existential level. This operation requires the training of skills related to the way of thinking and the way in which personal and Community educational actions are thought, in order to live uncertainty as one of positive and unavoidable human experience. In this regard, it is possible to identify an anthropological harmony between Morin's insights, phenomenology and psychoanalysis, referred in particular to issues of uncertainty, complexity and "ecology of action". The article, starting from a field experience in educational and formative ecosystems, aims to define a possible pedagogical anthropology's proposal, focused to the issues of uncertainty and complexity.